Exposure to childhood interpersonal trauma and mental health service urgency. (August 2020) - Marshall, Catherine; Semovski, Valbona; Stewart, Shannon L.
Abstract: Background: Children and youth with a history of maltreatment experience different developmental, psychiatric and health problems. Ensuring there is streamlined access to services is imperative to recovery. Yet, few reports of standardized methods for directing and prioritizing risk for children seeking services exist. Objective: The current study aims to address this gap and explore how mental health personnel triage highly vulnerable cases. Specifically, the goal of the current study is to examine whether experiencing childhood interpersonal trauma predicts service urgency. Participants and setting: Participants were 19, 645 children and youth, ages 4–18 years (M = 11.1 SD = 3.4) who completed the interRAI Child and Youth Mental Health Screener (ChYMH-S) at various community-based and residential children's mental health facilities across Ontario. Methods: Retrospective data collected from the ChYMH-S was used to explore differences in maltreatment history, gender, and legal guardianship and their impact on service prioritization. Results: Children and youth who were exposed to some form of interpersonal trauma were more likely to have mental health issues requiring urgent follow-up service compared to those who were not exposed. Findings also suggested that gender and legal guardianship impact service urgency. Conclusions: Children and youth who have experienced maltreatment are significantly more likely to score high on mental health service urgency than those who did not. This provides valuable insight that can support the development of appropriate system-level changes to policy and practice when servicing children and youth with mental health needs in Canada.